Biotic Supplements for Renal Patients: A Systematic Review and Meta-Analysis - Pisano, Anna; D’Arrigo, Graziella; Coppolino, Giuseppe; Bolignano, Davide (Nutrients, 2018)
Intestinal dysbiosis is highly pervasive among chronic kidney disease (CKD) patients and may play a key role in disease progression and complications. We performed a systematic review and meta-analysis to evaluate effects of biotic supplements on a large series of outcomes in renal patients. Ovid-MEDLINE, PubMed and CENTRAL databases were searched for randomized controlled trials (RCTs) comparing any biotic (pre-, pro- or synbiotics) to standard therapy or placebo. Primary endpoints were change in renal function and cardiovascular events; secondary endpoints were change in proteinuria/albuminuria, inflammation, uremic toxins, quality of life and nutritional status. Seventeen eligible studies (701 participants) were reviewed. Biotics treatment did not modify estimated glomerular filtration rate (eGFR) (mean difference (MD) 0.34 mL/min/1.73 m2; 95% CI −0.19, 0.86), serum creatinine (MD −0.13 mg/dL; 95% confidence interval (CI) −0.32, 0.07), C-reactive protein (MD 0.75 mg/dL; 95% CI −1.54, 3.03) and urea (standardized MD (SMD) −0.02; 95% CI −0.25, 0.20) as compared to control. Outcome data on the other endpoints of interest were lacking, sparse or in an unsuitable format to be analyzed collectively. According to the currently available evidence, there is no conclusive rationale for recommending biotic supplements for improving outcomes in renal patients. Large-scale, well-designed and adequately powered studies focusing on hard rather than surrogate outcomes are still awaited.